1988
DOI: 10.1200/jco.1988.6.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated epithelial-rich invasive malignant thymoma: complete response to cisplatin, vinblastine, and bleomycin therapy.

Abstract: Two cases of complete remission plus one almost complete and another partial response of undifferentiated, invasive epithelial malignant thymoma using the combination of cisplatin, vinblastine, and bleomycin (PVB), are reported in four patients treated with this combination. Radiotherapy was instituted after completing the fourth course of chemotherapy in three patients. One patient died from intercurrent infection after the fourth cycle of combination chemotherapy. Three patients remain free of disease at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The dismal prognosis of patients with advanced thymic carcinoma has made it necessary to experiment with new treatment modalities 5, 19. Recently, a good response rate to chemotherapy has been reported in the literature7, 20, 21 and multimodal strategies have been advocated 5, 8, 9, 19. Lucchi et al reported the results of multimodality treatment including neoadjuvant chemotherapy, surgery, and postoperative radiotherapy 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dismal prognosis of patients with advanced thymic carcinoma has made it necessary to experiment with new treatment modalities 5, 19. Recently, a good response rate to chemotherapy has been reported in the literature7, 20, 21 and multimodal strategies have been advocated 5, 8, 9, 19. Lucchi et al reported the results of multimodality treatment including neoadjuvant chemotherapy, surgery, and postoperative radiotherapy 19.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 4 patients with unresectable tumors at the time of presentation underwent complete resection with a good response using neoadjuvant chemotherapy, and all 4 patients were alive and free of disease with a follow‐up of 62–120 months. To our knowledge no recommended regimen of chemotherapy has been clearly established, although some authors have advocated a cisplatin‐ and/or doxorubicin‐based combination 7, 9, 11, 18, 20, 22. For advanced tumors that appear to be unresectable at the time of presentation, preoperative shrinkage of the thymic carcinoma by means of neoadjuvant chemotherapy may improve the resectability and, therefore, the survival rate.…”
Section: Discussionmentioning
confidence: 99%